2017
DOI: 10.3389/fphys.2017.00782
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Attenuates Atherosclerosis in a Partially Ligated Carotid Artery Mouse model via Regulating Angiotensin Converting Enzyme 2 Expression

Abstract: Hydrogen sulfide has been suggested to play an essential role in atherogenesis. There is a paucity of information about the association between H2S and angiotensin converting enzyme 2 (ACE2), a novel homolog of ACE. Therefore, the aim of the study was to explore the role of H2S in atherosclerosis with respect to ACE2 both in vitro and in vivo. Here, a murine model of acutely disturbed flow-induced atherosclerosis by left common carotid artery (LCA) partial ligation was utilized. We found that carotid partial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…Recently, H 2 S induces S-sulfhydration of kelch-like ECH-associated protein 1 (Keap1) and nuclear factor erythroid 2-related factor 2 (Nrf2) dissociation from Keap1, followed by Nrf2 nuclear translocation and anti-oxidize effects in endothelial cells, contributing to the ameliorating effect of H 2 S on atherosclerosis in the context of diabetes (Xie et al, 2016). Furthermore, in a mouse model of disturbed flow-induced atherosclerosis, application of H 2 S donor NaHS considerably attenuates the severity of atherosclerosis via upregulating expressions of angiotensin converting enzyme 2 (ACE2), thus converting pro-atherosclerotic Ang II to anti-atherosclerotic angiotensin 1-7 (Ang-(1-7)) (Lin et al, 2017). At the cellular level, NaHS promotes the expression of ACE2 to exert antiinflammatory properties in lipopolysaccharide (LPS)-stimulated endothelial cells, as pretreatment with a selective ACE2 inhibitor DX600 abrogates the anti-inflammatory effect of NaHS (Lin et al, 2017).…”
Section: H 2 S-related Endothelial Dysfunction In Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, H 2 S induces S-sulfhydration of kelch-like ECH-associated protein 1 (Keap1) and nuclear factor erythroid 2-related factor 2 (Nrf2) dissociation from Keap1, followed by Nrf2 nuclear translocation and anti-oxidize effects in endothelial cells, contributing to the ameliorating effect of H 2 S on atherosclerosis in the context of diabetes (Xie et al, 2016). Furthermore, in a mouse model of disturbed flow-induced atherosclerosis, application of H 2 S donor NaHS considerably attenuates the severity of atherosclerosis via upregulating expressions of angiotensin converting enzyme 2 (ACE2), thus converting pro-atherosclerotic Ang II to anti-atherosclerotic angiotensin 1-7 (Ang-(1-7)) (Lin et al, 2017). At the cellular level, NaHS promotes the expression of ACE2 to exert antiinflammatory properties in lipopolysaccharide (LPS)-stimulated endothelial cells, as pretreatment with a selective ACE2 inhibitor DX600 abrogates the anti-inflammatory effect of NaHS (Lin et al, 2017).…”
Section: H 2 S-related Endothelial Dysfunction In Atherosclerosismentioning
confidence: 99%
“…Furthermore, in a mouse model of disturbed flow-induced atherosclerosis, application of H 2 S donor NaHS considerably attenuates the severity of atherosclerosis via upregulating expressions of angiotensin converting enzyme 2 (ACE2), thus converting pro-atherosclerotic Ang II to anti-atherosclerotic angiotensin 1-7 (Ang-(1-7)) (Lin et al, 2017). At the cellular level, NaHS promotes the expression of ACE2 to exert antiinflammatory properties in lipopolysaccharide (LPS)-stimulated endothelial cells, as pretreatment with a selective ACE2 inhibitor DX600 abrogates the anti-inflammatory effect of NaHS (Lin et al, 2017). The results showed that endogenous H 2 S system was involved in the development of atherosclerosis.…”
Section: H 2 S-related Endothelial Dysfunction In Atherosclerosismentioning
confidence: 99%
“…Mani et al [96] proposed that H 2 S plays an anti-AS effect, which may inhibit intimal proliferation and adhesion molecule expression. Recently, a study also showed that NaHS notably activated angiotensin converting enzyme 2 (ACE2)-related pathways, so as to promote the transformation from pro-atherosclerosis to anti- atherosclerosis [116] .…”
Section: Pathophysiological Regulation Of H 2 S Onmentioning
confidence: 99%
“…In a mouse model of atherosclerosis induced by partial ligation of the left common carotid artery (LCA), NaHS administration significantly reduced the severity of atherosclerosis. This may be due to H 2 S up-regulating the expression of angiotensin converting enzyme 2 (ACE2) in the carotid artery, thereby converting angiotensin II to angiotensin 1-7 ( Lin et al, 2017 ). H 2 S can also inhibit atherosclerosis in ApoE (-/-) mice as well as the proliferation and migration of vascular smooth muscle cells (VSMCs) by upregulating plasma NO ( Lin et al, 2016 ).…”
Section: H 2 S and Cardiovascular Diseasesmentioning
confidence: 99%